2007
DOI: 10.1192/bjp.191.51.s102
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of first-contact psychosis in São Paulo, Brazil

Abstract: Incidence of psychosis in São Paulo was lower than expected for a large metropolis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0
24

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 24 publications
2
58
0
24
Order By: Relevance
“…They are at the upper end of rates reported in previous studies in low-and middle-income settings (see Table 1), including those that have used the most comparable methods. For example, studies in Brazil (Menezes et al 2007), Trinidad (Bhugra et al 1996), and Barbados (Mahy et al 1999) that applied the same inclusion criteria reported rates between 15 and 35/1 00 000 per year. It is notable that the highest reported rate is from the study in Barbados, whichas far as we could ascertain -was the only one that sought to extend case-finding to religious institutions.…”
Section: Psychoses Elsewherementioning
confidence: 99%
See 1 more Smart Citation
“…They are at the upper end of rates reported in previous studies in low-and middle-income settings (see Table 1), including those that have used the most comparable methods. For example, studies in Brazil (Menezes et al 2007), Trinidad (Bhugra et al 1996), and Barbados (Mahy et al 1999) that applied the same inclusion criteria reported rates between 15 and 35/1 00 000 per year. It is notable that the highest reported rate is from the study in Barbados, whichas far as we could ascertain -was the only one that sought to extend case-finding to religious institutions.…”
Section: Psychoses Elsewherementioning
confidence: 99%
“…It is unclear to what extent the apparent association between the incidence of psychoses and population density extends beyond the northern European cities in which it has been reported. Menezes et al (2007), for example, found a low rate of around 15/1 00 000 in a catchment area in Sao Paulo, one of the most densely populated cities in the world. The association, then, between psychoses and population density may be more complex than research to date suggests; investigating this further in a wider range of cities, across different continents, may provide novel insights into the kinds of environments that foster the development of psychoses.…”
Section: Psychoses Elsewherementioning
confidence: 99%
“…Schizophrenia is currently believed to be caused by a combination of genetic and environmental factors, which establish complex interactions during brain development 1,2 . The natural history of schizophrenia usually involves a prodromal period, when mild symptoms progressively increase in severity, duration and frequency until crossing a threshold, then allowing a diagnosis to be established in light of current nosological classification systems 3 .…”
Section: Introductionmentioning
confidence: 99%
“…1 In many countries psychiatric emergency services are frequently the first contact patients have with the health system or the main source of referral for the treatment of first-episode psychosis. 2 In Brazil, a study performed in the city of São Paulo showed that emergency services were the first contact of the patient with the health system in around 70% of the cases of first-episode psychosis, 3 and in around 50% of the cases this contact is made within up to four weeks of the onset of psychotic symptoms. 4 Some characteristics inherent to psychiatric emergency care may affect diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 99%